Non-newtonian fluid lens for wearable planewave ultrasound imaging system - Pisharody Harikrishnan Gopalakrishnan; Mahesh Raveendranatha Panicker (Biomedical Engineering Advances)
Ultrafast ultrasound imaging using planewaves has been found significant for many applications in the recent past. This work proposes a novel method for converging planewaves for wearable ultrafast ultrasound imaging systems using a concave non-Newtonian fluid lens. Due to the concave shape of the designed non-Newtonian fluid lens, ultrasound wave convergence on transmit can be achieved, which could enable deeper imaging with planewaves. Further, by employing multi-angle planewaves, a high-resolution high frame rate ultrasound imaging system can be developed. The proposed passive ultrasound converging lens demonstrated satisfactory performance for in vitro imaging (wire phantoms and steel screw phantoms) and in vivo imaging (human carotid artery and upper arm). The in vitro and in vivo results showed an improvement of 47.31 % of lateral resolution, 44.57 % of intensity with significant contrast to noise ratio improvement greater than 3 dB and observable drop in acoustic clutter levels at 7.6 MHz centre frequency. The proposed non-Newtonian fluid lens demonstrated 18 % of dehydration rate, suitable for continuous long period ultrasound imaging. The utility of the proposed approach was further confirmed by observing an increase in wave intensity with decreased radius of curvature values of the lens used in the system, which is of significance in focused ultrasound applications. The passive ultrasound non-Newtonian converging lens with the adjustable focusing capability, ergonomic design, and low cost of deployment without significantly altering the existing setup would open doors for upgradation of traditional systems to a wide range of applications in high frame-rate US imaging system.